Incidence and variables associated with short and long-term mortality in patients with systemic lupus erythematosus and sepsis admitted in intensive care units. (October 2018) - Abramovich, E; Barrett, O; Dreiher, J; Novack, V; Abu-Shakra, M
Background: Infections are common among patients with systemic lupus erythematosus (SLE), and are associated with increased morbidity and mortality. Objectives: To determine whether SLE is an independent risk factor for short- and long-term mortality in patients admitted to an intensive care unit (ICU) with sepsis, and to identify the characteristics of SLE patients admitted to an ICU with sepsis. Methods: A retrospective age- and sex-matched cohort study, based on data of the SEPSIS-ISR (Sepsis Israel) Registry, an ongoing study that collects data on all patients admitted with sepsis to the ICUs. The primary outcome was to determine whether SLE is an independent risk factor for 30-day and 3-year mortality. Secondary outcomes were 30-day and 3-year survival rates, and the identification of variables associated with mortality within the group of patients with SLE. Results: In total, 29 SLE and 87 non-SLE patients (median age 55 years; 79.3% females) were included. The primary sites of infection as well as pathogen distributions were similar between the two groups. The most common infections among the SLE and non-SLE patients were pneumonia (48.3 vs. 31%, p = 0.09), urinary tract infection (20.7 vs. 14.9%, p = 0.56) and peritonitis (13.8 vs. 16.1%, p = 0.77). Severe sepsis and septic shock were diagnosed in 79.3 versus 80.5% ( p = 0.89) and 55.2 versus 33.3% ( p = 0.04) of the SLE and non-SLE patients, respectively. The 30-day and 3-year survival rates did not differ between SLE and non-SLE patients, and were 69 versus 67.8% ( p = 0.79) and 41.4 versus 47.1% ( p = 0.69), respectively. In multivariate Cox regression analysis, age (hazard ratio (HR) = 1.02; 95% confidence interval (CI) 1.00–1.05) and cardiovascular involvement during sepsis (HR = 3.32; 95% CI 1.4–7.86) were significant independent risk factors for 30-day mortality. Multiorgan dysfunction during sepsis admission was associated with increased 3-year mortality (HR = 1.37; 95% CI 1.07–1.75). Conclusions: SLE is not an independent risk factor for 30-day or 3-year mortality following ICU admission with sepsis. Increased late mortality was associated with congestive heart failure within the SLE patients alone. None of the SLE-related variables were statistically different between the living and deceased SLE patients.